2017
DOI: 10.1007/s10994-017-5686-9
|View full text |Cite
|
Sign up to set email alerts
|

The online performance estimation framework: heterogeneous ensemble learning for data streams

Abstract: Ensembles of classifiers are among the best performing classifiers available in many data mining applications, including the mining of data streams. Rather than training one classifier, multiple classifiers are trained, and their predictions are combined according to a given voting schedule. An important prerequisite for ensembles to be successful is that the individual models are diverse. One way to vastly increase the diversity among the models is to build an heterogeneous ensemble, comprised of fundamentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 43 publications
3
75
0
Order By: Relevance
“…For example, Newbold and Granger (1974) use this approach for combining forecasters models. More recently, van Rijn et al (2018) proposed a method for data streams classification. As opposed to fusing experts, they select the best recent performing one to classify the next observation.…”
Section: Windowing Strategies For Expert Combinationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Newbold and Granger (1974) use this approach for combining forecasters models. More recently, van Rijn et al (2018) proposed a method for data streams classification. As opposed to fusing experts, they select the best recent performing one to classify the next observation.…”
Section: Windowing Strategies For Expert Combinationmentioning
confidence: 99%
“…Similar to WindowLoss, but selects the best expert in the last λ observations for prediction. van Rijn et al (2018) showed its competitiveness using streaming data; AEC:…”
Section: Ensemble Setup and Baselinesmentioning
confidence: 99%
“…Few concepts for automated algorithm selection on streaming data exist so far, both for supervised (see, e.g., van Rijn et al, 2014van Rijn et al, , 2018 and unsupervised learning algorithms. In unsupervised learning, stream clustering is a very active research field.…”
Section: Performance Measuresmentioning
confidence: 99%
“…The results indicated that ensemble method was more effective for diagnosing valvular heart disease. Rijn (19) build online performance estimation framework for dynamic data stream that weight the votes of individual classifiers members across the data stream and rely only on Hoeffding trees as base-level classifier. The performance was estimated using two functions based on window and fading factors.…”
Section: Related Workmentioning
confidence: 99%